Expression of Fox genes in the cephalochordate Branchiostoma lanceolatum - Aldea, Daniel; Leon, Anthony; Bertrand, Stephanie; Escriva, Hector (Frontiers in Ecology and Evolution, 2015)
Forkhead box (Fox) genes code for transcription factors that play important roles in different biological processes. They are found in a wide variety of organisms and appeared in unicellular eukaryotes. In metazoans, the gene family includes many members that can be subdivided into 24 classes. Cephalochordates are key organisms to understand the functional evolution of gene families in the chordate lineage due to their phylogenetic position as an early divergent chordate, their simple anatomy and genome structure. In the genome of the cephalochordate amphioxus Branchiostoma floridae, 32 Fox genes were identified, with at least one member for each of the classes that were present in the ancestor of bilaterians. In this work we describe the expression pattern of 13 of these genes during the embryonic development of the Mediterranean amphioxus, Branchiostoma lanceolatum. We found that FoxK and FoxM genes present an ubiquitous expression while all the others show specific expression patterns restricted to diverse embryonic territories. Many of these expression patterns are conserved with vertebrates, suggesting that the main functions of Fox genes in chordates were present in their common ancestor.